Utredning om ökade fjärrvärmeleveranser från Shell Raffinaderi AB genom installation av värmepump - Karlsson, Hanna (My University, 2002)
The aim of this diploma work is to investigate the possibilities to increase the waste heat recovery, by a suitable heat pump placement in the present heat recovery system at Shell Refinery in Göteborg. The heat recovery system includes 29 heat exchanger units, heating district heating water by cooling streams in the processes. When a heat pump is placed between the in- and outgoing district heating water streams, there is a relativity large collected amount of energy to be upgraded, which makes the use of large-scale equipment possible, without any need to invest in a new heat recovery system to collect heat from different sources. In the first part of this thesis, a MATLAB-model for the heat recovery system at Shell is created, which is based on a simplified heat transfer model for every heat exchanger, where the process streams also can be condensing. With help of the model, the possibilities for and the effects of different placements of the heat pump is investigated. The heat pump reduces the temperature of the incoming water and the process streams can then bee cooled to a larger extent and extract heat, which today is lost in air coolers, or results in products going to storage at an unnecessary high temperature. As a first criterion for a heat pump installation to be an interesting alternative, the effective coefficient of performance for the installation shall be larger than for a reference case, where e.g. lake water is used as a heat source. The results show that only one heat pump installation, including one single heat exchanger, gives a satisfying coefficient of performance. That is the heat exchanger ER-406, which is cooling gas oil before recirculation or storage. When the incoming water temperature is lowered by 5°C and 10°C, an increase in duty is obtained by 1 and 0.5 MW respectively. The increase in duty for this alternative is too small to be considered. As an alternative, a case is presented, where the total area of the above mentioned heat exchanger and two other heat exchangers, which have been identified to have a potential for increased heatrecovery, are increased by 100 %. This alternative gives a duty increase of 2.5 MW in total. In spite of the fact of the less satisfying coefficients of performance, a brief economic estimate was made for four of the larger heat pump installations
Keywords: Kemiteknik; Chemical Engineering